Analisis Diferensiasi Produk dan Persepsi Harga Donat Madu Cihanjuang (Studi Kasus Pada Konsumen Outlet Godean, Yogyakarta) - Kiki Norfiyanti (UPAJIWA DEWANTARA : Jurnal Ekonomi, Bisnis dan Manajemen Daulat Rakyat, 2021)
AbstractThis study aims to analyze product differentiation and price perseption. The study was conducted at Godean outlets. Respondents in this study were customers who purchased products at least once, respondents of Donat Madu Cihanjuang Godean as many as 63 people.This research belongs to the type of research with quantitative descriptive method. Based on the results of the study show that the product differentiation variable and price perception get very good criteria. On the product differentiation variable the highest value is obtained from the performance quality dimension, while the lowest value is the repairability dimension. The price perception variable the highest value is obtained from the dimensions of price and quality assumptions, while the lowest value is the affordable prices dimension.             This reseach suggestion is by giving knowladge to consumers about the ease of product repair, maintain product durability and maybe provide a guarantee in the event of a product defect and the last suggestion is review poduct prices for example providing promotional programs.                                                                                                                 Keywords: product differentiation, price perception